Conserved and specific features of Streptococcus pyogenes and Streptococcus agalactiae transcriptional landscapes - Rosinski-Chupin, Isabelle (BMC Genomics, 2019)
BACKGROUND: The human pathogen Streptococcus pyogenes, or group A Streptococcus, is responsible for mild infections to life-threatening diseases. To facilitate the characterization of regulatory networks involved in the adaptation of this pathogen to its different environments and their evolution, we have determined the primary transcriptome of a serotype M1 S. pyogenes strain at single-nucleotide resolution and compared it with that of Streptococcus agalactiae, also from the pyogenic group of streptococci. RESULTS: By using a combination of differential RNA-sequencing and oriented RNA-sequencing we have identified 892 transcription start sites (TSS) and 885 promoters in the S. pyogenes M1 strain S119. 8.6% of S. pyogenes mRNAs were leaderless, among which 81% were also classified as leaderless in S. agalactiae. 26% of S. pyogenes transcript 5′ untranslated regions (UTRs) were longer than 60 nt. Conservation of long 5′ UTRs with S. agalactiae allowed us to predict new potential regulatory sequences. In addition, based on the mapping of 643 transcript ends in the S. pyogenes strain S119, we constructed an operon map of 401 monocistrons and 349 operons covering 81.5% of the genome. One hundred fifty-six operons and 254 monocistrons retained the same organization, despite multiple genomic reorganizations between S. pyogenes and S. agalactiae. Genomic reorganization was found to more often go along with variable promoter sequences and 5′ UTR lengths. Finally, we identified 117 putative regulatory RNAs, among which nine were regulated in response to magnesium concentration. CONCLUSIONS: Our data provide insights into transcriptome evolution in pyogenic streptococci and will facilitate the analysis of genetic polymorphisms identified by comparative genomics in S. pyogenes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5613-5) contains supplementary material, which is available to authorized users.